2010
DOI: 10.1021/bc900470y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fusogenic Liposomes for Fluorescent Cell Labeling and Membrane Modification

Abstract: Efficient delivery of biomolecules into membranes of living cells as well as cell surface modifications are major biotechnological challenges. Here, novel liposome systems based on neutral and cationic lipids in combination with lipids modified by aromatic groups are introduced for such applications. The fusion efficiency of these liposome systems was tested on single cells in culture like HEK293, myofibroblasts, cortical neurons, human macrophages, smooth muscle cells, and even on tissue. Fusogenic liposomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 32 publications
1
112
0
Order By: Relevance
“…To assess the effect of lipids known to be enriched in caveolae, different Bodipy-labeled analogues of sphingolipids (Cer, SM C 5 and SM C 12 ), GSLs [ganglioside GM1 and lactosyl ceramide (LacCer)], Chol and phosphatidyl ethanolamine (PE) (Fig. S1B) were incorporated into liposomes [DOPE/Dotap/Bodipy-tagged lipid (47.5/47.5/5)] (Csiszar et al, 2010). Liposomes had diameters between 160-300 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect of lipids known to be enriched in caveolae, different Bodipy-labeled analogues of sphingolipids (Cer, SM C 5 and SM C 12 ), GSLs [ganglioside GM1 and lactosyl ceramide (LacCer)], Chol and phosphatidyl ethanolamine (PE) (Fig. S1B) were incorporated into liposomes [DOPE/Dotap/Bodipy-tagged lipid (47.5/47.5/5)] (Csiszar et al, 2010). Liposomes had diameters between 160-300 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CLVs possess unilamellar lipid bilayer membranes and can be produced with a wide range of uniform sizes through control of the flow-rates/applied pressures of the various component phases. After production, fragile molecules and biological components can be added to the surface for functionalization, or encapsulated into the SCMs using standard nano-vesicle fusion techniques 36,37 . Double emulsions can also be pre-functionalized or made to contain a stable drug compound before storage and then converted into CLVs at a later date when ready for use, allowing functional CLVs to be made in bulk and distributed to a wide variety of consumers for use as a cellular therapies, biosensors, and artificial cells.…”
Section: Resultsmentioning
confidence: 99%
“…We choose to work with the recently developed formulations reported by Csiszár et al because they were able to fuse with a large variety of cells. 29 Since the fusogenic activity of these systems is dependent on the use of uorescent lipids, fusion can be followed by the presence of uorescence in cells. Fig.…”
Section: Fusogenic Liposome Encapsulation Of Quantum Dotsmentioning
confidence: 99%
“…In this work, we adapted the freeze and thaw method to encapsulate water synthesized carboxyl-coated CdTe QDs in liposomes of different compositions. Recently, Csizár et al 29 reported direct fusion between non-functionalized cationic liposomes and the plasma membrane of different cell lineages. These liposomes with fusogenic properties are a valuable tool to investigate membrane fusion mechanisms and could also be used to design nanocarriers for intracellular delivery of membrane-impermeant compounds without the need for further chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%